Analysis of different criteria to size rainwater storage tanks using detailed methods - C. Santos (2013)
Normative and technical documents from Germany, United Kingdom and Portugal recommend the use of detailed methods to size storage tanks in rainwater harvesting systems. These methods are based on daily simulations of the systems operation using daily rainfall data and non-potable demand. However, scarce information is provided by these documents regarding the most appropriate criteria to obtain the rainwater storage tank when making the daily simulations. In this study, six different calculation methods are described and analyzed, including simplified procedures and detailed approaches with different criteria. To apply these methods, two cases of rainwater harvesting systems were used: a dwelling and a public building. Results show that methods based on the Maximum Rainwater Use and 100% Efficiency criteria result in very large storage volumes and very long payback periods. It appears that, amongst the analyzed criterions, the most appropriate to size a rainwater harvesting system through a daily simulation is the 80% Efficiency criteria, once it has the best ratio Economical savings/Installation cost. It was also concluded that Rippl method and the 80% Efficiency criteria lead to similar storage volumes.